Subsidies for the Brazilian musical press genesis and the history of the Independence Hymn, by Dom Pedro I (Per Musi, 2012)
This article aims at reviewing, through bibliographical and primary sources analysis, the history of one of Brazil ́s national anthems, the Independence Hymn, by Dom Pedro I, as well as bringing new subsidies for the study of the Brazilian musical press origins. It also intends to reveal some peculiarities of an early and lesser known piano and voice score of the Hymn, not present in today’s editions of this composition.